The Effect of Sales Growth, Capital Intensity, and Company Age on Tax Avoidance in Energi Sector Companies on The Indonesia Stock Exchange for The Period 2020-2022 - Bangsawan, Achdian Anggreny; Amiruddin, Nuraini; Husain, Amiruddin (Golden Ratio of Taxation Studies, 2025)
This study aims to analyze the effect of sales growth, capital intensity, and company age on tax avoidance in energy sector companies on the Indonesia Stock Exchange for 2020-2022. This study uses secondary data from financial statements with an observation period from 2020 to 2022. The number of companies sampled was 26 companies for three years, so the total observation data used was 78 samples. The sampling technique was carried out using a purposive sampling method. The data analysis method in this study uses multiple linear regression analysis with the help of the IBM SPSS version 30 program. Based on the research results, the variables of sales growth, capital intensity, and company age significantly affect tax avoidance. While sales growth has a negative and significant effect on tax avoidance, capital intensity does not affect tax avoidance, and company age has a positive and significant impact on tax avoidance.